PERPINDAHAN PANAS HYBRID PHOTOVOLTAIC DAN THERMOELEKTRIC GENERATOR DENGAN HOT MIRROR - Ardiansyah Ardiansyah; Mustofa Mustofa; Iskandar Iskandar; Andi Idhan; Yuli Asmi Rahman (Foristek, 2021)
Heat transfer is the transfer of energy from one area to another due to the temperature difference between these areas. Wasted heat energy can be converted into electricity using (TEG) between the hot and cold sides. If the temperature difference is more significant, the efficiency may increase along with the operating temperature of the TEG-type material. So in this study, the author will calculate the heat transfer that occurs in Photovoltaic (PV), Thermoelectric Generator (TEG), and Hot Mirrors by utilizing thermal energy light produced from Muxindo LED bulbs with 10 Watt, 15 Watt, and 20 Watt power. The results of this study indicate that by using 10, 15, and 20 Watt LED bulbs for free convection heat transfer, the power generated from each point increases because it passes through several obstacles from objects that experience a decrease in temperature to PV and TEG, with the characteristics of the displacement. The movement of molecules from the medium importance follows convection heat at every point of transfer in the intermediate substance. The most significant power generated from radiant heat transfer is about 0.1873 Watt. It occurs on the surface of the fresnel lens using a 20 Watt LED bulb with the characteristic that the radiation propagates in a straight line and does not require an intermediate medium to transfer heat from one substance to another. The most significant conduction heat transfer power, 0.2453 Watt, occurs in Fresnel Lens using a 20 Watt LED bulb with heat transfer characteristics in solid objects.